Slowing Down, Heating Up: Economic Deceleration and Social Discontent in Latin America - Albina, Iván (2025)
There have been widespread public expressions of discontent throughout Latin America since the early 2010s. We exploit harmonized microdata from national household surveys covering nearly all Latin American countries to explore potential sources of discontent driven by income changes along the income distribution. We also estimate fixed-effects models that link discontent measures to changes in household incomes. Our results suggest that discontent may stem less from absolute economic performance during the 2010s than from the significant deceleration relative to the previous decade.